Political Communication in Pandemic: The use of Twitter by Spanish regional presidents - Mateo-Toscano, Antonio; Marin-Dueñas, Pedro Pablo; Gómez Carmona, Diego (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
It is a fact that communication strategies in politics involve taking advantage of digital media and, more specifically, of social media, giving rise to politics 2.0. This paper analyses the communication that a sample of presidents of autonomous regions in Spain made on Twitter during the State of Alarm. Based on the methodology of content analysis, 1840 of their own tweets were analysed in order to determine what type of content they generated regarding the development of the health crisis, analysing how they said it and what topics they touched on.